2007
DOI: 10.1590/s0103-50532007000500012
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the internal conformational dynamics and solvation properties of cyclodextrins

Abstract: Simulações de dinâmica molecular são utilizadas para investigar a dinâmica conformacional interna e propriedades de solvatação das três ciclodextrinas naturais, α-, β-e γ-ciclodextrina em água e temperatura ambiente. Estes oligossacarídeos derivados da glicose apresentam uma estrutura molecular peculiar que lhes confere a habilidade de formar complexos de inclusão e modificar as propriedades físico-químicas das moléculas complexadas. As características estruturais das ciclodextrinas em solução são determinante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
2
10
0
1
Order By: Relevance
“…Neutron diffraction of crystalline β‐CD dodecahydrate showed on average 6.1 disordered water molecules inside the cavity27, 28 (Figure 3 c), in agreement with MD and Monte Carlo (MC) simulations 28. 29 The MD results further suggested that the number of water molecules inside the cavity roughly doubles per glucose unit, and that the residence time of an encapsulated water molecule is inversely proportional to the cavity size 30. Earlier simulations showed for α‐CD only 2–3 water molecules, and for γ‐CD more than for β‐CD, namely, 8.8 water molecules 29.…”
Section: Representative Concave Hosts With Hydrophobic Binding Consupporting
confidence: 75%
“…Neutron diffraction of crystalline β‐CD dodecahydrate showed on average 6.1 disordered water molecules inside the cavity27, 28 (Figure 3 c), in agreement with MD and Monte Carlo (MC) simulations 28. 29 The MD results further suggested that the number of water molecules inside the cavity roughly doubles per glucose unit, and that the residence time of an encapsulated water molecule is inversely proportional to the cavity size 30. Earlier simulations showed for α‐CD only 2–3 water molecules, and for γ‐CD more than for β‐CD, namely, 8.8 water molecules 29.…”
Section: Representative Concave Hosts With Hydrophobic Binding Consupporting
confidence: 75%
“…Numerous MD simulation studies have investigated the conformational dynamics and hydration of native and substituted CDs using various force fields like CVFF, 35 CSFF/CHARMM, 36 40 GROMOS, 41 44 GLYCAM98, 45 q4mdCD, 46 and OPLS. 47 , 48 The accuracy of the MD results, indeed, depends on the reliability of the underlying molecular model.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous MD simulation studies have investigated the conformational dynamics and hydration of native and substituted CDs using various force fields like CVFF, CSFF/CHARMM, GROMOS, GLYCAM98, q4mdCD, and OPLS. , The accuracy of the MD results, indeed, depends on the reliability of the underlying molecular model. Development of force field for carbohydrates had been a challenge to the computational chemists, compared to protein, lipids, or other biomolecules, owing to the conformational heterogeneity of carbohydrates. , A comparative study on the newer carbohydrate force fields reports equivalent performance of 53A6 GLYC , 56A6 Carbo_R , 2016H66, CHARMM36, and amber-based q4mdCD force fields in reproducing the structural details of CD, closely agreeing with the crystallographic data.…”
Section: Introductionmentioning
confidence: 99%
“…Neutronenstreuungsexperimente mit kristallinem β‐CD‐Dodecahydrat zeigten durchschnittlich 6.1 ungeordnete Kavitätswassermoleküle27, 28 (Abbildung 3 c), was mit den Resultaten von MD‐ und Monte‐Carlo(MC)‐Simulationen übereinstimmte 28. 29 Gestützt auf die MD‐Methode wurde die Vermutung angestellt, dass sich die Zahl der Kavitätswassermoleküle in etwa pro weitere Glucoseeinheit verdoppelt und dass die Verweilzeit der eingeschlossenen Wassermoleküle invers proportional zur Kavitätsgröße ist 30. Frühere Simulationen ergaben für α‐CD nur 2–3 Kavitätswassermoleküle und für γ‐CD mehr als für β‐CD, nämlich 8.8 29.…”
Section: Repräsentative Konkave Wirte Mit Hydrophoben Beiträgen Zuunclassified